Lightwave Control of Topological Properties in 2D Materials for Sub-Cycle and Non-Resonant Valley Manipulation - Jiménez-Galán; Silva, R. E.F.; Smirnova, Olga; Ivanov, M. (Optics InfoBase Conference Papers, 2021)
Using light fields tailored on a sub-cycle timescale to the symmetry of graphene-like materials, we show selective minimization of the bandgap at one of the valleys, introducing a new method for valleytronics and light-induced topology.
CRIS-Team Scopus Importer:2023-04-20